Aesthetic correction by composite resin, using mockup technique for the closure of diastemas; Case report - Viera, Kemberly Gabriela (2019)
The smile is the letter of presentation of an individual at present, and a suitable image manages to maintain a high self- esteem and quality of life; since if we lack an appropriate form and dental health this can lead to a depressed state by not being able to smile with confidence. Due to the progress in the dental processes these problems are already solved with an adequate treatment in the aesthetic discomfort of the patients. Both the dental clearance and the closure of diastemas are the processes most requested by people in terms of improving their aesthetic appearance refers to an adequate dental health is related to the appearance that is to say a balanced and bright teeth are the sample of a meticulous care and worried. The objective of this clinical case as the first point was to improve the aesthetics and self-esteem of the patient with a first-level treatment, with a diagnosis and procedure performed by specialists, and the second point is to provide a clinical guide, practice of how to solve this type of treatments with 100% success. The case presented a 26-year-old male patient who came to the consultation to treat the diastema and the coloring of his teeth. It is done after dental clarification to better stain dental pieces, proceeding to the closure of diastema with composite resin hybridized to achieve the point of contact. Best aesthetics and total patient satisfaction.